Letter (copy) : Help for Spain - Citrine, Walter, 1887-1983
030-0188-001 International. WMC/EAB/DT/450. 2nd May, 1938. Mr. G. Stolz, International Federation of Trade Unions, 9, Avenue D'Orsay, PARIS VIIe. Dear Comrade Stolz, HELP FOR SPAIN. I am greatly obliged to you for your letter of 29th April outlining the present position in Spain with regard to food supplies. I note that Comrade Schevenels will be sending me a more detailed report when he returns to the office this week. Yours sincerely, General Secretary. 292/946/30/188